2019
DOI: 10.1158/1538-7445.sabcs18-p5-04-13
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-04-13: Splicing factor ESRP1 controls ER-positive breast cancer progression by altering metabolic pathway genes

Abstract: Background Epithelial Splicing Regulatory Protein (ESRP1)is a key splicing factor that regulates Epithelial-to-Mesenchymal Transition (EMT) splicing program. Our previous study demonstrated that high levels of ESRP1 are associated with poor prognosis in human ER-positive (ER+) breast tumors in an independent manner of EMT process. We next explored the potential mechanisms that contribute to the role ESRP1 in endocrine therapy-resistant breast cancer. Methods Probe based-Human Transcriptome Array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The TF-miRNA co-regulatory network revealed that these prognosis-related RBPs might play important roles in BRCA. Indeed, studies have shown that CSTF3, 21 SIDT1, 7 ESRP1, 22 DDX39A, 23 NOP2, 24 NOVA1, 25 SFPQ, 26 and UBAP2L 27 participate in BRCA development and progression. Although the mechanisms still need to be defined, these studies support our prognostic models.…”
Section: Discussionmentioning
confidence: 99%
“…The TF-miRNA co-regulatory network revealed that these prognosis-related RBPs might play important roles in BRCA. Indeed, studies have shown that CSTF3, 21 SIDT1, 7 ESRP1, 22 DDX39A, 23 NOP2, 24 NOVA1, 25 SFPQ, 26 and UBAP2L 27 participate in BRCA development and progression. Although the mechanisms still need to be defined, these studies support our prognostic models.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial splicing regulatory proteins 1 and 2 (ESRP1 and ESRP2) manipulate tumor epithelial-to-mesenchymal transition (EMT). This is also a side effect of the possible association of PHGDH with tumorigenic EMT [37] . Ma et al demonstrated that glucose restriction induces PHGDH phosphorylation by p38 at Ser371, and in clinical pancreatic cancer specimens, the phosphorylation levels of PHGDH-Ser371 and PHGDH-Ser55 correlated with p38 and AMPK activity, respectively [38] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, overexpression of ESRP1 and ESRP2 in basal-like breast cancer cells resulted in upregulation of E-cadherin expression, while in an ER-negative breast cancer model (MDA-MB-231 cells), low ESRP1 expression was associated with the development of EMT. In contrast, ESRP1 drove invasiveness in ER+ breast cancers independent of EMT, and thus, high ESRP1 expression but not ESRP2 was significantly associated with reduced overall survival in breast cancer patients as well as with poor prognosis in ER+ breast cancers, suggesting that the malignant phenotype of human breast cancer is associated with ESRP1 overexpression ( 42 , 43 ).…”
Section: Mechanism Of Rbps In Breast Cancermentioning
confidence: 99%
“…ESRP1 and/or ESRP2 further promote EMT by regulating the selective splicing of Rac1 and CD44. In breast cancer, the reduction of ESRP1 changes the variant expression of CD44v from CD44v to CD44, thus inhibiting its metastasis in the lung ( 42 , 43 ). In addition, HnRNP M can promote the expression of mesenchymal-specific CD44v through competitive interaction with ESRP1, thereby promoting breast cancer metastasis ( 25 , 34 ).…”
Section: Function Of Rbps In Breast Cancermentioning
confidence: 99%